«WHAT MEANS FOR YOU MY SIMPLE NAME?»: IDENTIFICATION OF THE HERO IN POETIC GENRES - Ольга Королькова (Докса, 2017)
The main objective of this research is to study subject’s names as an identifier of a hero in a literary work. The role of the hero’s name in different literary genres is examined, the fundamental importance of the name for characterizing the image, the characteristics of cultural discourse, and the ideological design of the work is revealed. Special attention is drawn to try to investigate the genre of love lyrics, where the functioning of the proper name as an identity marker is especially problematic, which leads to its replacement by pronouns. The study is based on the semiotic concepts of Yu. M. Lotman and B. A. Uspensky, as well as the theory of the lyrics of T. I. Silman. It is shown that in the love lyric the proper name, which can be considered as a special mythological layer of the verbal language as a whole, loses its mythological character, and the pronoun as its palliative acquires this mythology. As a result of the study, it can be concluded that the semiotics of the proper name and its palliatives reveals the mythological mechanisms of semiosis in the discourses of literature.